A non-local structural derivative model for memristor. (September 2019) - Qiu, Lin; Chen, Wen; Wang, Fajie; Lin, Ji
Highlights: A new mathematical model is employed to portray the memory effect of memristor. The given model with two-degree-of-freedom added is more effective and flexible. The provided model can describe special case like the ultra-weak memory effect. A novel drift function is proposed and a more practical model is generated. Abstract: The memristor is of great application and significance in the integrated circuit design, the realization of large-capacity non-volatile memories and the neuromorphic systems. This paper firstly proposes the non-local structural derivative memristor model with two-degree-of-freedom increased to portray the memory effect of memristor. Actually, the developed is a more generalized model that will be reduced to the classical one when the fractal characteristic index α  = 1. The proposed model is more flexible than the classical ideal memory model and Riemann Liouville memristor model under the same conditions. In addition, the memory effect described by the present scheme could be adjusted by the position parameter δ . This work provides a new methodology not only to describe the memory effect of the memristor, but also to easily portray the memristor with ultra-weak memory.